The Use of Instagram Through the Perceived Learning Experiences of @mike.thechameleon's Followers in Enhancing English-Speaking Learning Motivation - Yuhinis, Baiq Ilil; Amrullah; Junaidi, Ahmad (LITPAM, 2026)
This study aims to explore the perceived learning experiences of followers of the Instagram account @mike.thechameleon in learning English speaking and how these experiences shape their learning motivation. This research employed a qualitative descriptive approach. The data were collected through an open-ended questionnaire consisting of ten questions and semi-structured interviews involving 30 followers of @mike.thechameleon. The data were analysed thematically to identify recurring patterns in participants’ learning experiences, while the before-and-after self-rating scale results were used as descriptive support to illustrate changes in speaking aspects. The findings indicate that participants' experiences can be categorized into positive and negative experiences, with positive experiences being more dominant. Positively, participants perceived learning through the account as easy and useful short lessons, increased confidence and reduce anxiety, increased learning motivation, and a fun, relaxed, and non-formal learning environment, supported by short video content, repetition, and speaking challenges. The findings also reveal that three speaking aspects were influenced, namely fluency, pronunciation, and accuracy, with pronunciation showing the strongest improvement. in general, Instagram through the @mike.thechameleon account serves as a supportive supplementary learning medium that contributes to participants’ speaking development and learning motivation, particularly in pronunciation improvement.